Rancang Bangun Prototipe Sistem Pemantau Kondisi Kesehatan Pasien Berbasis Web - Sri Mulyono (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2013)
Prototype web-based health monitoring was constructed to monitor the patient's health remotely in real time. Arduino was used to take physical data from patients and convert it into electronic data then sent to the server by using ethernet shield. Based on the result in the research, it was found that body temperature and pulse of the patients were possibly to display into web page in the form of numbers and graphics within seconds (+ 28 seconds). This system also possibly sent alarm information by SMS in seconds (+ 62 seconds). This health monitoring system could be accessed from various range of devices such as notebook, Smartphone and any possible devices compatible with flash in the web. The system was also capable of measuring body temperature and pulse rate with no significant difference compared with manual measurements on a 5% significance level (p> 0,05). Based on this research, it can be inferred that this health monitoring system can provide real-time and accurate medical information anywhere and anytime.